Researching precarious, virtual and clandestine labour: Methodological and ethical challenges. (14th May 2022) - Iphofen, Ron; Huws, Ursula; Spencer, Neil. H.
Abstract : Introducing this volume, this article reflects on recent changes that brought to the editors' attention the need for this special issue on the methodological and ethical challenges facing those who research precarious, virtual and clandestine labour in the 21st century. An exponential spread of algorithmically managed platform labour, just-in-time working, micro-work, teleworking and other trends associated with digitalisation has converged with traditional patterns of work in the informal economy, including clandestine practices, such as the use of child labour, trafficked labour and slave labour, to create a dynamically shifting labour market that cannot be captured by traditional means using existing indicators. Simultaneously, digitalisation has introduced the possibility of new research methods, raising new ethical challenges, as well as stimulating the adaptation of older forms of ethnographic research including participant observation and action research. It discusses the articles in this issue, suggesting that they form the basis of an ongoing debate.